Partial S substitution activates NiMoO4 for efficient and stable electrocatalytic urea oxidation. Issue 75 (18th August 2020) - Han, Wen-Kai; Li, Xiao-Peng; Lu, Li-Na; Ouyang, Ting; Xiao, Kang; Liu, Zhao-Qing
Abstract : Achieving a profound understanding of the reaction kinetics of a catalyst by modulating its electronic structure is significant. Abstract : Achieving a profound understanding of the reaction kinetics of a catalyst by modulating its electronic structure is significant. Herein, we present a scalable approach to achieving a spatially partial substitution of S into NiMoO4 . The increase in active components in a true Ni 3+ oxidation state as a result of optimizing the coordination environment greatly improved urea oxidation activity.